PENINGKATAN KEMAMPUAN BERPIKIR KRITIS MELALUI MODEL AUDITORY, INTELLEKTUALY, REPATITION (AIR) BERBANTUAN KOMIK IPA DI SEKOLAH DASAR - Yunita Sari; Zulela MS; Vina Iasha; Jeane Kalengkongan (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2020)
This study aims to improve critical thinking skills by using Auditory, Intellectually, Repatition (AIR) learning models assisted by science comics. This research is a Classroom Action Research (CAR). The subjects of the research were the fifth grade students of Beji 03 Public Elementary School, totaling 27 students. Data collection techniques include tests in the form of evaluation questions and non-test techniques, using observation. Data analysis of critical thinking skills using evaluation questions. To calculate the increase in students using a normalized Gain test. The results obtained by students' critical thinking skills, in the first cycle completeness of 40.74% and the average achieved by 58.96 then in the second cycle the completeness of students increased to 85.18% and the average achieved to be 73.70 it can be concluded that the use of the Auditory learning model, Intellectually, Repatition (AIR) assisted by science comics can improve the critical thinking skills of fifth grade students of Beji 03 Elementary School.